2015
DOI: 10.3329/bjpbg.v26i2.23848
|View full text |Cite
|
Sign up to set email alerts
|

CHARACTER ASSOCIATION IN F4 GENERATION OF RICE (Oryza sativa L.)

Abstract: Twenty five rice genotypes were used to study the genetic components, correlation and path coefficients during Aman season of 2011. Thirteen characters were studied to find out the suitable traits for the improvement of rice yield. Among these characters considerable correlation were observed. Correlation values of grain yield per square meter with plant height, number of tillers per hill, number of panicles per hill, panicle length, number of primary branches, number of filled grain per panicle, spikelet ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 4 publications
6
12
0
Order By: Relevance
“…Furthermore, in contrast to our results, they reported a significant positive correlation between PL and GP. Similar to the results of current work, a significant positive correlation between PH and PL was found by Hossain et al, (2015) and Kishore et al, (2015) while, Rai et al, (2015) reported it significant, but negative. According to our observations and in agreement with Hossain et al, (2015), the correlation between GW and GP was significant and positive while, Kishore et al, (2015) reported it significantly negative.…”
Section: Conventional and Sequential Path Analysissupporting
confidence: 81%
“…Furthermore, in contrast to our results, they reported a significant positive correlation between PL and GP. Similar to the results of current work, a significant positive correlation between PH and PL was found by Hossain et al, (2015) and Kishore et al, (2015) while, Rai et al, (2015) reported it significant, but negative. According to our observations and in agreement with Hossain et al, (2015), the correlation between GW and GP was significant and positive while, Kishore et al, (2015) reported it significantly negative.…”
Section: Conventional and Sequential Path Analysissupporting
confidence: 81%
“…The real genetic difference in yield and its components between genotypes are expected and found also by Anis et al (2016b); Prasad et al (2015) and Rai et al (2015).…”
Section: B Effect Of Genotypessupporting
confidence: 64%
“…The analysis of variance revealed a wide range of variability of the studied traits regarding selected drought-tolerant leafy vegetable amaranths. A wide range of variability was also reported in red and green color amaranth (33), rice (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56), maize (57)(58)(59), and coconut (60,61). The lowest moisture content was noted in the salt-tolerant vegetable amaranth genotypes LS9 and LS7.…”
Section: Discussionmentioning
confidence: 99%